A novel hypoxia response element regulates oxygen-related repression of tissue factor pathway inhibitor in the breast cancer cell line MCF-7. Issue 157 (September 2017) - Cui, Xue Yan; Skretting, Grethe; Tinholt, Mari; Stavik, Benedicte; Dahm, Anders Erik Astrup; Sahlberg, Kristine Kleivi; Kanse, Sandip; Iversen, Nina; Sandset, Per Morten
Abstract: Background: Hypoxia is one of the most pervasive physiological stresses in solid tumors. We have previously demonstrated that tissue factor (TF) pathway inhibitor (TFPI) expression was transcriptionally repressed by the activation of hypoxia inducible factor (HIF)-1α under hypoxic conditions. However, the role of HIF-2α, also known as endothelial PAS domain-containing protein 1 (EPAS1), on TFPI expression remains unclear. Aim: To explore the role of HIF-2α/EPAS1 in the regulation of TFPI expression under hypoxia in breast cancer cells. Methods and results: Quantitative RT-PCR showed that total TFPI mRNA and protein levels were decreased by the overexpression of HIF-2α/EPAS1 in MCF7 cells. Luciferase reporter assay and chromatin immunoprecipitation (ChIP) assay indicated a HIF-2α/EPAS1 responsive region located in the TFPI promoter region at − 170 to + 21 relative to the transcriptional start site. Subsequent mutagenesis demonstrated a functional hypoxia response element (HRE) 5′-AAACAGGA-3′ for HIF-2α/EPAS1 within the TFPI promoter located at − 45 to − 38. In breast cancer patients, a positive correlation between HIF-2α/EPAS1 and total TFPI mRNA expression was observed by using gene expression analysis. Conclusions: This study provides evidence that HIF-2α/EPAS1 is involved in the regulation of TFPI gene expression in breast cancer cells, suggesting that the activation of coagulation and the increased risk of thrombosis observed in breast cancer patients may correlate with local hypoxic regulation of coagulation factors and their inhibitors. Highlights: HIF-2a plays a role in hypoxia mediated regulation of TFPI in MCF-7 cells. HIF-2α transcriptionally repressed TFPI via a functional hypoxia response element. The mRNA level of HIF-2α correlated to the mRNA level of TFPI in breast cancer.